2002
DOI: 10.4049/jimmunol.168.6.2953
|View full text |Cite
|
Sign up to set email alerts
|

IL-13-Induced Chemokine Responses in the Lung: Role of CCR2 in the Pathogenesis of IL-13-Induced Inflammation and Remodeling

Abstract: IL-13 stimulates inflammatory and remodeling responses and contributes to the pathogenesis of human airways disorders. To further understand the cellular and molecular events that mediate these responses, we characterized the effects of IL-13 on monocyte chemotactic proteins (MCPs) and compared the tissue effects of transgenic IL-13 in mice with wild-type (+/+) and null (−/−) CCR2 loci. Transgenic IL-13 was a potent stimulator of MCP-1, -2, -3, and -5. This stimulation was not specific for MCPs because macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
159
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(175 citation statements)
references
References 50 publications
(74 reference statements)
13
159
2
Order By: Relevance
“…1C). As previously reported (30,31), IL-13 significantly increased the levels of mRNA encoding these chemokines in IL-13 Tg mice with WT IL-13R␣2 loci (Fig. 1C).…”
Section: Role(s) Of Il-13r␣2 In Il-13-induced Pulmonary Inflammationsupporting
confidence: 69%
See 1 more Smart Citation
“…1C). As previously reported (30,31), IL-13 significantly increased the levels of mRNA encoding these chemokines in IL-13 Tg mice with WT IL-13R␣2 loci (Fig. 1C).…”
Section: Role(s) Of Il-13r␣2 In Il-13-induced Pulmonary Inflammationsupporting
confidence: 69%
“…Studies in a variety of systems have demonstrated that IL-13 is a major mediator of these fibrotic responses (42,51,56). A number of studies demonstrated that IL-13 causes tissue fibrosis, at least in part, by inducing and activating TGF-␤1 (22,32), which is dependent on MCP-1/CCL2 and MMP-9, respectively (30,32). The present studies add to our understanding of this important fibrogenic pathway by demonstrating that IL-13R␣2 plays a critical role in its regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokines and their receptors associated with a Th1 response, e.g., RANTES and IFN-inducible protein-10, were increased, attracting neutrophils, monocytes, and lymphocytes (18,19). In contrast, the chemokines expressed by 10/12 KO mice, including MCP-2, MCP-3, and MCP-5, as well as TARC, C10, eotaxin, and eotaxin 2, are increased in mice with enhanced IL-13 expression and mice lacking IFN-␥ (18,20). Likewise, MIP-1␥ has been associated with a Th2 phenotype (18).…”
Section: Discussionmentioning
confidence: 84%
“…A significant increase in versican accumulation occurs in the interstitial space of small and large airways of patients with asthma (11-13, 15, 46) and in animal models of asthma (17,18). Cells isolated from diseased lungs also exhibit altered versican production.…”
Section: Discussionmentioning
confidence: 99%